ACCOMPANIMENT / LEGAL ASSISTANCE OF BUSINESS LICENSING OF NOSTALGIA COFFEESHOP THROUGH OSS SYSTEM - Excel Brayen Sandoval; Lu Sudirman (Universitas Internasional Batam, 2022)
After the enactment of Law no. 11 of 2020 concerning Job Creation, as has been followed up with PP No. 7 of 2021 concerning the Ease, Protection, and Empowerment of Cooperatives and Micro, Small, and Medium Enterprises, it has been regulated that